Artemisia annua L. aqueous extract as an alternative to antibiotics improving growth performance and antioxidant function in broilers. Issue 1 (14th December 2020) - Guo, Shiwei; Ma, Jiaxin; Xing, Yuanyuan; Xu, Yuanqing; Jin, Xiao; Yan, Sumei; Shi, Binlin
Abstract: Due to a series of problems, such as drug resistance and tissue residue caused by adding antibiotics to feed, this research aimed to study the effects of Artemisia annua L. aqueous extract (AAE) as an alternative to antibiotics on growth performance and antioxidant capacity of broilers. A total of 240 one-day-old mixed-sex Arbour Acres broilers were randomly allotted into six groups with five replicates of eight birds each. These six diets were formulated by adding 0, 500, 1000, 1500, 2000 mg/kg AAE and 50 mg/kg chlortetracycline (CTC) to the basal diet, respectively. Average daily body weight gain (ADG), average daily feed intake (ADFI), and feed conversion ratio (FCR) were measured. Total antioxidant capacity (T-AOC), the activity of catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and the concentrations of malondialdehyde (MDA) were determined, and the relative gene expression in tissues was measured. The polyphenol flavonoid contents and in vitro antioxidative results showed that: the total phenolic and flavonoid contents were 39.58 ± 6.01 mg GAE/g, 7.04 ± 0.55 mg RE/g, respectively. The inclusion of AAE increased ADG, the activities of T-AOC, CAT, SOD and GSH-Px, and the gene expression of antioxidant enzymes, the concentrations of MDA decreased in serum and tissues. In conclusion, AAE can be used as a feed additive due to its capability to improve growth performance, antioxidant function in broilers. Dietary inclusion of 1000–1500 mg/kg AAE can be used as an alternative for antibiotic growth promoter replacement without negative effect on broiler performance. Highlights: Artemisia annua L. aqueous extract can promote growth performance and antioxidant function of Broilers. Artemisia annua L. aqueous extract is expected to become the substitute for antibiotics and promote the growth of the body. The optimal dose range of Artemisia annua L. aqueous extract in diet of broilers was 1000–1500 mg/kg.